A culture of light : cinema and technology in 1920s Germany - Guerin, Frances (University of Minnesota Press ; [University Presses Marketing, distributor], 2005)
In Frances Guerin's history of German silent cinema of the 1920s, the use of light is the pivot around which a new national cinema and culture emerges. Guerin's interpretations center on use of light in films such as Metropolis (1926) and Der Golem (1920) and we see how light is the substance of image composition, the narrative structuring device, and the thematic concern. Choice Outstanding Academic Title.